Pretty little girls - Ruff, Jenifer (Middletown, DE: Greyt Companion Press, 2019)
"The disappearance of a prep school girl from an affluent family leads to a world of hidden secrets more shocking and horrifying than anyone could imagine. FBI Agent Victoria Heslin is called to Charlotte, NC to investigate alongside local police, but the mysteries only get deeper. Why are the girl's parents so uncooperative? And why are the local authorities resisting Victoria's help? When her efforts uncover a sex trafficking operation, Heslin enlists friend and fellow Agent Dante Rivera to go rogue and try to save the girls, before it's too late."
Book cover
Keywords: Human tracfficking -- Fiction; Missing person -- Fiction